Vibrations of table tennis racket composite wood blades: modeling and experiments - Manin, L.; Poggi, M.; Havard, N. (Procedia Engineering, 2012)
This study is concerned with table tennis racket used in competitions. Table tennis racket blades are made of an assembly of several wood layers (3, 5 or 7). The layers are of different wood essences, and the fiber orientations of successive layers are perpendicular most of the time. Hence, the blades appear to be made of a composite material. A finite elements analysis was conducted on the modeling of the racket blade. The questions relative to the detailed modeling of each wood layer is discussed versus the modeling of only one homogenized layer. The model considered orthotropic properties for the wood material. The elasticity orthotropic properties of each of the wood essences used were determined individually. Also, global properties of blade samples were measured. These quantities were then used for the material properties specifications in the FE model. The simulations performed gave the mode shape for the resonance frequencies. In parallel, an experimental analysis was performed to determine the resonance frequencies and the vibration mode shapes for several boundary conditions: racket handle clamped, and racket freely supported. The excitation of the racket blade has been done both by using a shock hammer and by performing a sine sweep with a shaker. The comparisons between vibration modes and frequencies obtained by simulation and experiment permit to validate a FE model for the racket blade. It takes into account the orthotropic property of the composite wood that constitutes the blade.